Kolaborasi Pengembangan Pariwisata Desa Sawarna - Kusen Kusen; Ahmad Sihabudin; Juliannes Cadith (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
This article will discuss the involvement of actors in tourism development in Sawarna Village. The tourist destinations in Sawarna Village have become a new tourist icon that can be visited by tourists. However, it seems that it has not appeared in the public space as the main destination. Of course there are a number of obstacles that arise. The research method used in this study is a qualitative method with a case study approach. Borrowing a term from J.W. Creswell (2013) who suggested that a strategic approach that can be used to facilitate qualitative research such as the case study approach (Creswell, 2013). As a result, the government has not been committed to developing tourism, because the accessibility obtained by other actors, such as academics, the community, the media and entrepreneurs has not been maximized. In fact, these actors have a significant role, so that tourist destinations can also be integrated ideally.